HIV-associated disseminated histoplasmosis successfully treated with isavuconazole consolidation therapy - Mazzella, Andrea (Med Mycol Case Rep, 2019)
A 30-year-old man with advanced HIV and disseminated histoplasmosis deteriorated after stepping down from intravenous liposomal amphotericin B to itraconazole. Therapeutic levels of itraconazole and posaconazole were not achieved, therefore liposomal amphotericin B was reintroduced. Stepdown treatment was switched to oral isavuconazole; since then the patient has remained well.